Preventing Disasters and Displacement: How Economic, Social, and Cultural Rights Can Advance Local Resilience. Issue 1 (2nd January 2022) - Cullen, Miriam; Munro, Jane
Abstract: This article builds on the widespread recognition that disaster is not a 'natural' phenomenon but occurs where exposure to a particular hazard coincides with pre-existing vulnerabilities to it—which might be social, economic or environmental—to increase personal susceptibility to harm. It argues that the impacts of climate change impose an increasingly pressing need to revive the realisation of economic, social and cultural rights as a priority, not only through their express incorporation into disaster risk planning, policies and domestic law, but by rethinking how they are implemented to include and empower the people who need them most.